Cultured Neonatal Murine Primary Myotubes as a Model to Study Muscle Atrophy. Issue 11 (28th November 2022) - Tamta, Ankit Kumar; Shivanaiah, Bhoomika; Ningaraju, Sunayana; Prabhashankar, Arathi Bangalore; Sundaresan, Nagalingam Ravi
Abstract: Besides genetic disorders, skeletal muscle atrophy mainly occurs as a consequence of underlying conditions such as prolonged inactivity, aging, and metabolic diseases, ultimately contributing to the risk of disability. Disturbances in cellular and molecular mechanisms involved in proteolysis and protein synthesis underpin muscle fiber shrinkage and decreased muscle fiber diameter. Stress‐induced primary myotube culture is an established model for studying muscle atrophy. An in vitro model is an essential criterion in establishing preliminary data in a cell‐autonomous manner that can later be validated using in vivo models. Here, we describe protocols for the isolation, culture, and differentiation of primary murine myotubes and the induction of myotube atrophy using dexamethasone, a synthetic corticosteroid. We further elaborate the procedure to validate degenerative parameters, such as assessing muscle fiber diameter, expression of muscle atrophy genes, and protein synthesis status under dexamethasone treatment. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Isolation and culture of primary myoblasts from rat or mouse pups Support Protocol 1 : Preparation of coated tissue culture ware Support Protocol 2 : Subculture of myoblasts Basic Protocol 2 : Induction and assessment of myotube atrophy